1749 Safety Netting Information for the Acutely Sick Child: Systematic Literature on Effectiveness. (October 2012) - Lakhanpaul, M; Neill, S; Shang, C; Thompson, M
Abstract : Background and Aims: Uncertainty and anxiety surround parents' decisions to seek medical help for a sick child at home because parents are concerned not to miss serious illness whilst also not bothering the doctor unnecessarily. This dilemma leads to parents' desire for more information to support their decision making. Factors influencing the success of information resources need to be identified prior to the development of safety netting interventions for families. The ASK SNIFF team (Acutely Sick Kid Safety Netting Interventions for Families) aimed to review the literature on the effectivenss of existing resources to provide an evidence base for the develoment of safety netting information for parents to be used when determining to seek help for an acutely sick child. Methods: The initial stage of the project involved a systematic review using narrative analysis to identify influences on the effectiveness of information resources for parents caring for an acutely ill child at home. Results: A range of measures for effectiveness have been used in the literature which limits their comparison. Interventions that included information on more than one illness or symptom were found to be more effective. Parents were more likely to act on information provided to them in the community than in the emergency department. Co- created information by parents and health professionals were found to be more successful. Conclusions: Safety netting information resources may be more effective if they are designed with parents and their content, mode and place delivery is evidence based.